Cardiovascular and renal effects of apelin in chronic kidney disease: a randomised, double-blind, placebo-controlled, crossover study - Chapman, Fiona A.; Melville, Vanessa; Godden, Emily; Morrison, Beth; Bruce, Lorraine; Maguire, Janet J.; Davenport, Anthony P.; Newby, David E.; Dhaun, Neeraj (Nature communications, 2024)
Chronic kidney disease (CKD) affects ~10% of the population and cardiovascular disease is its commonest complication. Despite treatment, patient outcomes remain poor and newer therapies are urgently needed. Here, we investigated the systemic and renal effects of apelin in CKD. In a randomized, double-blind, placebo-controlled, crossover study, 24 subjects (12 patients with CKD and 12 matched healthy subjects) received pyroglutamated apelin-13 ([Pyr 1 ]apelin-13, 1 nmol/min and 30 nmol/min) or matched placebo on two separate visits. Systemic and renal hemodynamics were monitored throughout. The co-primary endpoints were change in systemic vascular resistance index and renal blood flow. Secondary endpoints were change in blood pressure, cardiac output, pulse wave velocity, glomerular filtration rate, natriuresis, free water clearance and urinary protein excretion. In both health and CKD, 30 nmol/min [Pyr 1 ]apelin-13 reduced mean arterial pressure by ~4%, systemic vascular resistance by ~12%, and increased cardiac index by ~10%, compared to placebo (p < 0.05 for all). Both doses of [Pyr 1 ]apelin-13 increased renal blood flow by ~15%, natriuresis by ~20% and free water clearance by ~10%, compared to placebo (p < 0.05 for all). In patients with chronic kidney disease only, glomerular filtration rate fell by ~10%, effective filtration fraction by ~5% and proteinuria by ~25% (p < 0.01 for all). Apelin has short-term cardiovascular and renal benefits in CKD. If maintained longer-term, these should improve patient outcomes. Clinical trials of long-acting oral apelin agonists are justified in CKD and other conditions with impaired salt and water balance. Registration number at www.clinicalTrials.gov : NCT03956576. Funded by Kidney Research UK. Despite treatment, patients with chronic kidney disease remain at high risk of kidney failure and cardiovascular disease. Here, the authors show that apelin offers potential cardiorenal protection for this high-risk patient group.